EMPOWERING STUDENT’S CREATIVE WRITING ABILITY BY USING CANVA - Mustika Larasati (Journal of English Education Program (JEEP), 2022)
The present study was aimed to investigate how teacher teaches creative writing by using Canva and what are student‟s perception on the use of Canva as media in learning writing. The present study used qualitative design with the type of case study. The data were obtained through several sources such as observation which was conducted once to observe how teacher used Canva as media in teaching creative writing. The two others were questionnaire and interview that were employed to collect data about student‟s perception on the use of Canva as media. Eighteen students from 8th grade and one English teacher participated in this study. The observation data and interview were transcribed, coded, interpreted. Meanwhile, the questionnaire data was analyzed using Likert Scale measurement. The findings revealed that, to implement Canva in teaching writing, the teacher used constructivism.Moreover, from interview and questioner about student‟s perception showed that the use of Canva as teaching media could make them more motivated in learning and also enrich their knowledge in using media. Based on the findings,the writer suggested that teacher should use media, especially Canva in their teaching activity, to motivate their students and enrich their knowledge on using various digital media.